Patient safety - Abd Hamid, Harris Shah (Pearson Malaysia, 2012)
Diseases and sickness are part of a normal life. It is also normal to seek treatment for afflictions. However, qUite surprisingly, it is also normal for people to be exposed to additional harms in the process of being treated. A study of British hospitals revealed that 10.8% of patients admitted to hospitals experienced unintended injuries caused by medical mismanagement (Vincent, Neale, & Woloshynowych, 2001). Patients experienced single or multiple injuries that led to mild impairments, permanent impairments, and even death. Shockingly, 48% of the unintended injuries, or adverse events, were preventable.